2021
DOI: 10.3390/ani11051224
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Mycobacterium avium Subspecies paratuberculosis Positive Milk Antibody ELISA Results in Dairy Cattle under Varying Time Periods after Skin Testing for Bovine Tuberculosis

Abstract: Enzyme-linked immunosorbent assays (ELISA) are used to screen cows for Mycobacterium avium subspecies paratuberculosis (MAP) infections, informing Johne’s disease (JD) management practices in dairy herds. The causative agent of bovine tuberculosis (bTB), Mycobacterium bovis, and MAP share multiple antigens. Moreover, Mycobacterium avium subspecies avium is used in the single intradermal cervical comparative tests (SICCT) that are routinely used in early detection of cows infected with bTB. Although these are d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 24 publications
(33 reference statements)
1
5
0
Order By: Relevance
“…A recent study performed by Barden et al (2020) showed an increase in the odds of a positive MAP test result when MAP milk ELISA testing occurs less than 30 d to SICCT testing. A similar result was also found by Bridges and van Winden (2021), who reported an increased risk of testing positive in the MAP milk ELISA, with a gradually increasing risk, peaking 57 to 70 d post SICCT testing to subsequently wain. In this study, we aim to further characterize the relationship between SICCT testing and MAP milk ELISA performance, including an assessment of whether the immunological response to the SICCT test is different for MAP-infected cows and noninfected cows.…”
Section: Introductionsupporting
confidence: 85%
“…A recent study performed by Barden et al (2020) showed an increase in the odds of a positive MAP test result when MAP milk ELISA testing occurs less than 30 d to SICCT testing. A similar result was also found by Bridges and van Winden (2021), who reported an increased risk of testing positive in the MAP milk ELISA, with a gradually increasing risk, peaking 57 to 70 d post SICCT testing to subsequently wain. In this study, we aim to further characterize the relationship between SICCT testing and MAP milk ELISA performance, including an assessment of whether the immunological response to the SICCT test is different for MAP-infected cows and noninfected cows.…”
Section: Introductionsupporting
confidence: 85%
“…31 Monitoring the humoral immune response by bPTB-ELISA provides faster results and is a cheaper alternative to other diagnostic tools to detect infected animals. 8,10 However, different studies have questioned the usefulness of the technique due to its limited accuracy, 10,12,15,32,33 which should be considered when designing a bPTB control programme. 1,7 Different studies showed that the SE and SP values of the bPTB-ELISA ranged between 7% and 94% and 40% and 100%, respectively, 8,12 depending on the test, the sample used in the reference test (faeces or intestinal tissues), age or clinical stage of infection, 8,11 interference with other mycobacteria [14][15][16] or the time elapsed between the test and the SIT test.…”
Section: Discussionmentioning
confidence: 99%
“…1,7 Different studies showed that the SE and SP values of the bPTB-ELISA ranged between 7% and 94% and 40% and 100%, respectively, 8,12 depending on the test, the sample used in the reference test (faeces or intestinal tissues), age or clinical stage of infection, 8,11 interference with other mycobacteria [14][15][16] or the time elapsed between the test and the SIT test. 13,17,32,33 In the present study, microbiological culture of intestinal tissue (ileocaecal lymph nodes and ileocaecal valve, respectively) was used as a reference test, in contrast to most studies using faecal samples. However, tissue culture is more sensitive than faecal culture, allows detection of animals in the early stages of infection, is a postmortem technique to confirm the diagnosis of positive animals 11 and is also used to validate rapid diagnostic tests.…”
Section: Discussionmentioning
confidence: 99%
“…It should be highlighted that in addition to M. bovis- infection, performing a TST can also influence MAP-positive results in tested animals. It is possible that TST could boost the antibody response and increase the sensitivity of paratuberculosis ELISA results [ 10 , 24 ]; this would indicate that at least some of the results were not false positives. However, the limited number of serological studies in Poland have found the seroprevalence of paratuberculosis in cattle to be much lower (1–3%) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that exposure to environmental NTM can reduce the specificity of M. bovis diagnostic tests [ 9 ]. However, only a few studies [ 10 , 11 ] have examined the inverse relationship: the effect of MTBC infection on MAP diagnostic results.…”
Section: Introductionmentioning
confidence: 99%